Which metal represents the greatest risk to freshwater ecosystem in Bohai Region of China?. Issue 2 (22nd February 2017) - Su, Chao; Lu, Yonglong; Johnson, Andrew C.; Shi, Yajuan; Zhang, Meng; Zhang, Yueqing; Juergens, Monika D.; Jin, Xiaowei
Abstract: Metals discharged from industrial effluents, agricultural wastewater, and sewage runoff by rapid urbanization are of concern as contaminants of freshwater ecosystem because of their persistence and high toxicity to aquatic organisms. This study attempted to identify which metal posed the greatest risk to freshwater ecosystem in the Bohai Region, China. The metals arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), zinc (Zn), lead (Pb), nickel (Ni), mercury (Hg), iron (Fe), and manganese (Mn) were compared against norfloxacin and gamma‐hexachlorocyclohexane (lindane). By comparing the median reported environmental and ecotoxicity concentrations, it showed that Cu, Fe, Zn, Mn, and Cr were the top five metals of concern. Of these, Cu was deemed to represent the highest risk and Hg the lowest risk. The risks for all metals were higher than those for norfloxacin and lindane. Almost all the metals except Hg had water concentrations that exceeded levels where ecotoxicity effects had been recorded in the literature. A comparison with the measurements across the UK rivers suggested that all metals examined had water concentrations about 5‐ to 10‐fold higher than the UK median values except for Cu, Fe, Cd, and Pb. The Fuyang River, a tributary of the Haihe River Basin, seemed to be the location with the highest metal concentrations. However, comparing the post‐2010 period to 2000–2009, concentrations of all the metals had fallen except for Fe and Mn, so risks have decreased over the last 7 yr with the greatest improvements for Cd and Pb. While metals still pose high risks to freshwater ecosystem in this region, there is encouragement that some control measures are taken into effect.